Evaluation of morphological parameters and bioactive compounds in different varieties of beetroot (Beta vulgaris L. ssp. esculenta GURKE var. rubra L.) - Rubóczki, T.; Raczkó, V.; Takácsné Hájos, M. (International Journal of Horticultural Science, 2015)
Beetroot consumption based on pickled beets generally in Hungary which is due to the higher yield from second crop harvested in autumn and processed by manufacturing industry. Researches of the past years confirmed its favourable nutritional-physiological effects on human body so demands, as for fresh salad, also increased. The trial aimed at testing the interaction of varieties on quality parameters and in the same time suggestions are made how to use different varieties of beetroot according to its quality. Morphological and sensory evaluations were examined on 10 varieties of beetroot harvested in autumn. The regular spherical shape can reduce the refining loss during the processing of beetroot which is beneficial for the manufacturing industry. In our trial the root shape of Libero, Mona Lisa and Rubin varieties approached most the regular spherical shape (diameter/length – 1.0) which is favoured by not only processing industry but also fresh market. The highest red pigment content (betanin) was observed in Mona Lisa, Akela and Cylindra (34.58–47.66 mg/100 g). A similar trend could be observed in yellow pigments (vulgaxanthins) which proves the close correlation between the quantities of the two pigments (r=0.898). Highest total polyphenol (77.13–83.37 mg GAE/100g) and flavonoid (21.73–22.73 mg CE/100g) contents were detected in Akela, Mona Lisa and Bonel. These varieties are favourable for fresh salad and they can satisfy processing requirements also. Highest water soluble solids content was found in Akela (7.15%). In our conditions nitrate (NO3-N) values below 900 mg/kg were examined in all of the varieties which is favourable in the case of beetroot.